Beyond Exchange: Decoding Reciprocal Hospitableness in Luxury Lodge Experiences - Manfreda, Anita; Harkison, Tracy-Lesley (Elsevier, 2025)
Hospitableness in luxury hospitality is key for guest experience differentiation. Despite increasing attention, limited research has investigated how hospitableness is reciprocated and how such reciprocation extends beyond the guest-host relationship. By employing a multiple-case study design, this study proposes a model of reciprocal hospitableness underpinning the luxury lodges experience from a multi-stakeholder perspective. The findings reveal how hospitableness, which includes aspects like altruism/generosity, sense of belonging/fictive kinship, meaningful connection, comfort/homely atmosphere, and inclusivity, is reciprocated among guests, hosts, and other stakeholders, uncovering the practices and behaviours that promote this mutual exchange. The model contributes to theory and practice on hospitableness, social exchange and reciprocity, transformative luxury research, and sustainable luxury. It emphasises hospitableness as essential for the luxury lodging industry's sustainability, impacting economic, environmental, and social aspects. It advocates for reciprocal hospitableness, involving guests, staff, local communities, and environments in reshaping luxury tourism's impact.
Keywords: 1504 Commercial Services; 1506 Tourism; 3504 Commercial services; 3508 Tourism; Luxury hotel; Social exchange; Hospitableness; Transformative luxury research; Reciprocity; Sustainable luxury